1984
DOI: 10.1111/j.1365-2559.1984.tb02342.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous adenocarcinoma in anorectal fistulae

Abstract: Mucinous adenocarcinoma arising in an anorectal fistula is an uncommon condition which gives rise to difficult problems of diagnosis and pathogenesis. The clinical history and pathology of seven patients are described and compared with six patients in whom anal fistulae were lined by normal rectal mucosa or 'misplaced glands'. In five of the cases granulomas were present which were a further cause of diagnostic difficulty. The evidence from this study suggests that the fistulous tracks are congenital duplicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Adenocarcinomas and squamous-cell carcinomas have both arisen in nonhealing fistula tracts (Table 4). 7,8,[18][19][20][21][22][23][24][25][26][27] Long-standing fistulas of the gastrointestinal and bronchopulmonary systems have been the most widely affected by malignant transformation. [28][29][30] Chronic infection and inflammation (i.e., Crohn's disease and radiation) are the most frequently associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinomas and squamous-cell carcinomas have both arisen in nonhealing fistula tracts (Table 4). 7,8,[18][19][20][21][22][23][24][25][26][27] Long-standing fistulas of the gastrointestinal and bronchopulmonary systems have been the most widely affected by malignant transformation. [28][29][30] Chronic infection and inflammation (i.e., Crohn's disease and radiation) are the most frequently associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis after APR is generally good, probably because of the propensity of this tumor to be well differentiated and slow growing, and the rarity of metastasis to lymph nodes. 6 In conclusion, biopsy of any anal tumor is undoubtedly essential for diagnosis, although it often fails to provide diagnostic evidence of mucinous carcinoma. Thus, surgical decisions about mucinous carcinoma should be based on clinical manifestations, imaging fi ndings, and cytology of mucin obtained by drainage even when it is diffi cult to obtain malignant cells in multiple biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the diagnosis of mucinous adenocarcinoma is often delayed because of failure to obtain biopsy evidence. [5][6][7] As the cancer cells are usually present in clusters fl oating in a mucous lake, deep and multiple biopsies of fi stulous tracts or perianal masses are often necessary to establish the diagnosis. We report a case of mucinous adenocarcinoma associated with an anal fi stula, in which histological analysis of the resected specimen provided important insight into the distribution of the mucin and cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al in 1984 studied the histology of patients in whom they found normal rectal mucosa, or 'misplaced' glands lining anal fistula [4]. He postulated that these fistulous tracts are congenital duplications of the lower third of the hind gut lined by rectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous adenocarcinoma of the perianal region is a rare cancer, constituting 3%-19% of all anal carcinomas [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It is even rarer still that a mucinous adenocarcinoma is found to be arising from a chronic anorectal fistula, with few reports in the literature.…”
Section: Introductionmentioning
confidence: 99%